2000
DOI: 10.1074/jbc.m001193200
|View full text |Cite
|
Sign up to set email alerts
|

RhoA and Rho Kinase Regulate the Epithelial Na+/H+ Exchanger NHE3

Abstract: The activity of the Na ؉ /H ؉ exchanger NHE3 isoform, which is found primarily in epithelial cells, is sensitive to the state of actin polymerization. Actin assembly, in turn, is controlled by members of the small GTPase Rho family, namely Rac1, Cdc42, and RhoA. We therefore investigated the possible role of these GTPases in modulating NHE3 activity. Cells stably expressing NHE3 were transiently transfected with inhibitory forms of Rac1, Cdc42, or RhoA and transport activity was assessed using microfluorimetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(19 citation statements)
references
References 42 publications
(38 reference statements)
0
19
0
Order By: Relevance
“…These data suggest that, in intact epithelial monolayers, ezrin phosphorylation after initiation of Na ϩ -glucose cotransport requires Akt activity. Rho kinase is known to phosphorylate ezrin (9) and has also been implicated in NHE3 inhibition (22,41). Thus, we considered the possibility that rho kinase regulates the coordinate activation of ezrin and NHE3 after initiation of Na ϩ -glucose cotransport.…”
Section: Akt Inhibition Prevents Ezrin Phosphorylation After Initiatimentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that, in intact epithelial monolayers, ezrin phosphorylation after initiation of Na ϩ -glucose cotransport requires Akt activity. Rho kinase is known to phosphorylate ezrin (9) and has also been implicated in NHE3 inhibition (22,41). Thus, we considered the possibility that rho kinase regulates the coordinate activation of ezrin and NHE3 after initiation of Na ϩ -glucose cotransport.…”
Section: Akt Inhibition Prevents Ezrin Phosphorylation After Initiatimentioning
confidence: 99%
“…For example, NHE3 knockout mice suffer from mild diarrhea and are acidotic and hypotensive (20). NHE3 activity can be regulated by the actin cytoskeleton (21)(22)(23). Although this may be caused in part by regulation of NHE3 at the plasma membrane, it is also clear that translocation of NHE3 to the plasma membrane contributes significantly to NHE3 up-regulation (24,25).…”
mentioning
confidence: 99%
“…6K and O). It has been reported that ROCK1 phosphorylates and activates Na + /H + exchanger isoform 1, NHE1 Denker et al, 2000) and that Rho-kinases inhibit the activity of Na + /H + exchanger isoform 3 (NHE3), another type of ion exchanger (Szászi et al, 2000). Because NHE1 and NHE3 are localized on the plasma membrane in MDCK cells (Noel et al, 1996) and NHE1 is in the mouse endometrial epithelium (Wang et al, 2003), it is likely that the ROCK1 localized on the plasma membrane may participate in phosphorylating these substrates.…”
Section: Plasma Membranementioning
confidence: 99%
“…However, the mechanisms by which DA acutely reduces NHE3 activity have not been examined. Redistribution of NHE3 transporters has been shown to mediate regulation of NHE3 activity in intact kidney (48 -54), in cultured renal epithelial cells (55,56), and in transfected fibroblasts (57)(58)(59)(60)(61)(62)(63)(64). In addition, although NHE phosphorylation has been associated with changes in NHE3 activity (52,(65)(66)(67)(68), and phosphorylation appears to be functionally important for regulation of NHE3 activity by pharmacologic activators of protein kinases in transfected fibroblasts (65)(66)(67), the physiologic significance of NHE3 phosphorylation is still undetermined.…”
mentioning
confidence: 99%